2011
DOI: 10.1016/s1836-9553(11)70005-4
|View full text |Cite
|
Sign up to set email alerts
|

Gaming console exercise and cycle or treadmill exercise provide similar cardiovascular demand in adults with cystic fibrosis: a randomised cross-over trial

Abstract: ACTRN12610000861055.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
114
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(124 citation statements)
references
References 23 publications
4
114
0
Order By: Relevance
“…Our data are in line with other reports. 15,18,22 In addition, our results suggest that a type of training such as a stationary cycle is an efficient way to train cardiovascularly, but it may not be an effective exercise program if children with CF do not enjoy it and, as such, have poor participation. We showed that interaction, presence of feedback, and variation in the exercise program influence enjoyment.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Our data are in line with other reports. 15,18,22 In addition, our results suggest that a type of training such as a stationary cycle is an efficient way to train cardiovascularly, but it may not be an effective exercise program if children with CF do not enjoy it and, as such, have poor participation. We showed that interaction, presence of feedback, and variation in the exercise program influence enjoyment.…”
Section: Discussionmentioning
confidence: 81%
“…In the literature, there are few articles about use of active video games in subjects with CF. Kuys et al 22 showed that Nintendo Wii induced significantly higher maximum and minimum heart rates compared with cycle ergometry or treadmill exercise in 19 adults with CF admitted to the hospital. In that study, subjects enjoyed the gaming console more than standardcare exercise.…”
Section: Discussionmentioning
confidence: 99%
“…For HR evoked during exercise we used a difference of 10 beats per minute (bpm) (i.e. -10 to +10bpm) for our equivalence margins as there is no agreed-upon minimum important difference and two previous studies nominated a difference of 10bpm as important when performing their initial sample size 9 calculations [27,28]. For dyspnoea, equivalence margins of 1 unit (i.e.…”
Section: Data Synthesismentioning
confidence: 99%
“…There were five studies [27][28][29]56,58] which examined acute effects of a single session of AVGs. For most of these the active video game was compared to traditional exercises [27][28][29]61], though some compared AVGs to maximal [58] or submaximal exercise tests [56].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation